2021
DOI: 10.2196/31358
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Perspectives on the Impacts of COVID-19: Social Media Content Analysis

Abstract: Background Nurses are at the forefront of the COVID-19 pandemic. During the pandemic, nurses have faced an elevated risk of exposure and have experienced the hazards related to a novel virus. While being heralded as lifesaving heroes on the front lines of the pandemic, nurses have experienced more physical, mental, and psychosocial problems as a consequence of the COVID-19 outbreak. Social media discussions by nursing professionals participating in publicly formed Facebook groups constitute a valua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 67 publications
0
26
0
2
Order By: Relevance
“…Research results prove that nursing students can understand how to prevent COVID-19 after being given health education and campaigns in preventing COVID-19 (Albaqawi et al, 2020). It is also corroborated by Koren et al, (2021) that it is crucial to apply the latest knowledge in protecting healthcare professionals and nursing staff caring for patients with COVID-19; Health care providers should educate nurses/other health workers about the dangers of communicable diseases, including proper use of personal protective equipment, proper personal hygiene practices, and related environmental measures.…”
Section: Discussionmentioning
confidence: 54%
“…Research results prove that nursing students can understand how to prevent COVID-19 after being given health education and campaigns in preventing COVID-19 (Albaqawi et al, 2020). It is also corroborated by Koren et al, (2021) that it is crucial to apply the latest knowledge in protecting healthcare professionals and nursing staff caring for patients with COVID-19; Health care providers should educate nurses/other health workers about the dangers of communicable diseases, including proper use of personal protective equipment, proper personal hygiene practices, and related environmental measures.…”
Section: Discussionmentioning
confidence: 54%
“…emotions or issues), considering their change over time, we have missed the opportunity to quantify their intensity systematically (e.g. using machine learning, algorithm, or sentiment analysis) 18 , 19 or adopting other coding models than content analysis. 35 For example, future studies should adopt the coding scheme proposed by Cutrona and Russell 72 to analyse the type of social support (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…exhaustion, frustration, anger and depression). 18 Moreover, Elyashar et al have examined online discussions on their topics and emotions, as reported among 53,063 Twitter profiles by different health care providers (including nurses) during 2020 and compared them with 2019. The authors described that most of the discussions were related to the professional implications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Os principais pontos levantados pelos enfermeiros foram: desinformação divulgada pela mídia; Equipamentos de Proteção Individual (EPIs) inadequados; efeitos colaterais dos EPIs e efeitos do teste positivo para a COVID-19. Assim como nesta pesquisa, esses fatores impactaram, negativamente, a saúde física, mental e psicossocial dos enfermeiros, gerando sofrimento emocional, raiva, ansiedade, frustração, solidão e isolamento (Koren et al, 2021).…”
Section: Discussionunclassified